Non-operative management after chemoradiotherapy plus consolidation or sandwich (induction with bevacizumab and consolidation) chemotherapy in patients with locally advanced rectal cancer: a multicentre, randomised phase II trial (NOMINATE trial). Issue 3 (18th March 2022) - Akiyoshi, Takashi; Shinozaki, Eiji; Taguchi, Senzo; Chino, Akiko; Hiratsuka, Makiko; Tominaga, Tetsuro; Nonaka, Takashi; Toda, Shigeo; Matoba, Shuichiro; Matsui, Shimpei; Okabayashi, Koji; Mukai, Toshiki; et al.
Abstract : Introduction: Total mesorectal excision (TME) and postoperative adjuvant chemotherapy following neoadjuvant chemoradiotherapy (CRT) is the standard treatment for locally advanced rectal cancer (LARC). However, neoadjuvant CRT has no recognised impact on reducing distant recurrence, and patients suffer from a long-lasting impairment in quality of life (QOL) associated with TME. Total neoadjuvant therapy (TNT) is an alternative approach that could reduce distant metastases and increase the proportion of patients who could safely undergo non-operative management (NOM). This study is designed to compare two TNT regimens in the context of NOM for selecting a more optimal regimen for patients with LARC. Methods and analysis: NOMINATE trial is a prospective, multicentre, randomised phase II selection design study. Patients must have clinical stage II or III (T3-T4Nany) LARC with distal location (≤5 cm from the anal verge or for those who are candidates for abdominoperineal resection or intersphincteric resection). Patients will be randomised to either arm A consisting of CRT (50.4 Gy with capecitabine) followed by consolidation chemotherapy (six cycles of CapeOx), or arm B consisting of induction chemotherapy (three cycles of CapeOx plus bevacizumab) followed by CRT and consolidation chemotherapy (three cycles of CapeOx). In the case of clinical complete response (cCR) or near cCR, patients will progress to NOM. Response assessment involves a combination of digital rectal examination, endoscopy and MRI. The primary endpoint is the proportion of patients achieving pathological CR or cCR≥2 years, defined as the absence of local regrowth within 2 years after the start of NOM among eligible patients. Secondary endpoints include the cCR rate, near cCR rate, rate of NOM, overall survival, distant metastasis-free survival, locoregional failure-free survival, time to disease-related treatment failure, TME-free survival, permanent stoma-free survival, safety of the treatment, completion rate of the treatment and QOL. Allowing for a drop-out rate of 10%, 66 patients (33 per arm) from five institutions will be accrued. Ethics and dissemination: The study protocol was approved by Wakayama Medical University Certified Review Board in December 2020. Trial results will be published in peer-reviewed international journals and on the jRCT website. Trial registration number: jRCTs051200121